Cause, Pattern and Outcome of Fractures Occurring in the Pediatric Population of Rural Tertiary Health Care Center of Nepal - Karki, Dhan Bahadur; Rokaya, P.K.; Rawal, M.; Bhandari, P.B.; Limbu, D.; Shrestha, S.; Acharya, B.D.; Thapa, S.D. (Journal of Karnali Academy of Health Sciences, 2018)
Introduction: Pediatric trauma is a significant burden to health care worldwide. In Karnali province, most of the cases present late. The aim of this study is to determine demographic characteristics, cause, pattern, treatment and outcome of pediatric fractures in tertiary health care center in Jumla. Methods: This is a retrospective study done in patients younger than 16 years who presented to our hospital between January 2016 to December 2017. We analyzed demographic data, injury characteristics, fracture pattern, time of presentation, treatment modalities and outcome. Results: There were total of 1028 patients out of which 60% were males. Mean duration of presentation to hospital was 4.8 days. Most common mechanism of injury was fall from height. 85.60 % were managed conservatively and 14.40% were managed operatively. Postoperative outcome was good in 71 % of the cases, fair in 28% and poor in 1% cases. Forearm fracture was the most common presentation, accounting for 358 cases (34.82%) followed by Supracondylar humerus fracture accounting 23.34%. Conclusions: Pediatric fractures constitute a huge proportion of cases in our hospital. As pediatric bones unite readily, the treatment outcome is good in most of the cases even after conservative management and after delayed presentation.